PENGARUH STRUKTUR ASET, AKTIVITAS, DAN LEVERAGE TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR KESEHATAN PADA MASA PANDEMI COVID-19 - Ragil Tarys Kusuma Landryani; Agustinus Kismet Nugroho Jati (FEB Universitas Sam Ratulangi Manado, 2023)
This study aims to determine and analyze the effect of asset structure, activity, leverage, and COVID-19 on the profitability of health sector companies. The research method used was purposive sampling. The sample used was 13 health sector companies listed on the Indonesia Stock Exchange with annual data for the 2015-2021 period according to the established criteria. Analysis was performed using multiple regression analysis with four independent variables and one dependent variable. The results of this study indicate that asset structure, activity, and leverage have a significant negative effect on profitability, while Covid-19 has an insignificant positive effect on profitability. Keywords: Asset Structure, Activity, Leverage, Covid-19, Profitability.